Pelatihan Upaya Kesehatan Kerja Bagi Masyarakat Cipayung Kota Depok - Azizah Musliha Fitri; Fajaria Nurcandra; Terry Yuliana Rahadian Pristya (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
An initial survey that had been done found that the location of the settlement where residents of cipayung lived was very close to the location of the Cipayung Landfill. The unhealthy environment tended to cause disease and any other health problems, so that efforts needed to be made to overcome this, one effort that could be done is training on health . This counseling activity was attended by 21 residents living in the village of West Bulak which is the closest residential location to the Cipayung landfill site. Wilcoxon test results on the pre-test and post-test scores of participants showed a P- value of 0.001 which means that there were differences in the level of knowledge of the participants after attending counseling. The average value of pre-test and post-test had a difference of 34.5 shows that counseling that has been carried out is able to increase knowledge.